Smallholder Livelihoods, Wealth and Deforestation in the Eastern Amazon. - Pacheco, P. (2009)
In this paper, I examine patterns of wealth accumulation and their influence on deforestation among smallholders at Uruará and Redenção, in the state of Pará in the Brazilian Eastern Amazon. I argue that the development of the smallholder economy has not been a linear process, and the diversity of smallholder farming systems and their patterns of wealth accumulation have varied implications for the rate and magnitude of deforestation. However, whilst there are differential impacts of farming practices on deforestation—cattle ranching has a greater impact than cash cropping or subsistence agriculture—the stronger correlate of deforestation is the wealth of the farmers. Wealthier farmers not only tend to deforest more in absolute terms, but also show a slightly greater propensity to deforest whatever their production system. Though cattle production is a key driver of wealth accumulation and thus deforestation, a significant number of smallholders adopt diversified production systems. The main factors explaining the relationship between the farming systems and deforestation were years of residence on the lot, distance of the lot to main market and the amount of day labor hired—and not variables describing household structure.